2018
DOI: 10.1186/s12879-017-2923-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices on Schistosomiasis in sub-Saharan Africa: a systematic review

Abstract: BackgroundSchistosomiasis remains a global health problem with an estimated 250 million people in 78 countries infected, of whom 85% live in Sub-Saharan Africa. Preventive chemotherapy remains the key public health strategy to combat schistosomiasis worldwide. Recently the WHO emphasized on the use of integrative approaches in the control and elimination of schistosomiasis. However, a detailed understanding of sociocultural factors that may influence the uptake of the intended health activities and services is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 56 publications
11
97
2
Order By: Relevance
“…High levels of awareness have been found consistently in other surveys across sub-Saharan Africa [2125], including one in neighbouring Cabo Delgado province, Mozambique [26]. A recently published systematic review on schistosomiasis KAP in sub-Saharan Africa concluded, however, that high awareness is typically coupled with poor knowledge of causes, prevention and control [27]. This pattern was also found in the four study districts at baseline [16] and it was therefore encouraging to see generally improved knowledge at endline.…”
Section: Discussionmentioning
confidence: 75%
“…High levels of awareness have been found consistently in other surveys across sub-Saharan Africa [2125], including one in neighbouring Cabo Delgado province, Mozambique [26]. A recently published systematic review on schistosomiasis KAP in sub-Saharan Africa concluded, however, that high awareness is typically coupled with poor knowledge of causes, prevention and control [27]. This pattern was also found in the four study districts at baseline [16] and it was therefore encouraging to see generally improved knowledge at endline.…”
Section: Discussionmentioning
confidence: 75%
“…Misconceptions about transmission were rife including thoughts that it was through witchcraft, and that directly bathing children with river water fetched in containers was not a risk factor. Some misconceptions and gaps in knowledge have been quantified in Uganda [15, 21] and elsewhere [22]. This is glaring evidence that the caregivers and probably many people in the endemic communities are not comprehensively knowledgeable about the modes of transmission for the schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as this tool does not involve any quality assessment score, we used the shortened version from Sacolo, Chimbari, & Kalinda [16], consisting of 10 yes/no questions, resulting in a total score to give a quality rating from 1-4 (Low), 5-7 (Moderate) to 8-10 (High). The details of this assessment per item/question and the total quality score for each study are presented in Table 1.…”
Section: Insert Figure 1 Herementioning
confidence: 99%